Innovative Strategies to Support Mental Wellbeing - Victoria Y. McCue (Library & Knowledge Services and Nursing & Health Sciences Research Departments, 2020)
The Coronavirus disease 2019 (COVID-19) pandemic has adversely affected many people's mental wellbeing. COVID-19 has led healthcare organizations to reconceptualize and reform healthcare through an innovative lens that will foster resilience. Finding strategies to support mental wellbeing, especially for frontline clinicians, is crucial to ensure a comprehensive recovery. This manuscript describes innovative strategies implemented within one healthcare organization in the Southeastern United States to nurture mental wellbeing for the community and frontline healthcare clinicians.